Evaluating the effectiveness of natural wastewater treatment systems from intensive trout aquaculture facilities - Marcin Sidoruk; Ireneusz Cymes; Skwierawski Andrzej; Mirosław Skorbiłowicz (Water Resources and Industry)
With the intensification of aquaculture and its environmental consequences, natural wastewater treatment methods are gaining increasing importance. This study assessed the effectiveness of two nature-based solutions (treatment ditches and sedimentation ponds) in improving the quality of effluents from four trout farms. Water quality parameters were analyzed before and after treatment, focusing on nitrogen compounds, organic matter, total suspended solids, and oxygen dynamics. Statistical analyses revealed significant correlations between selected indicators. Treatment ditches were particularly effective in removing nitrogen compounds, notably ammonia and nitrite, while sedimentation ponds showed greater efficiency in reducing organic matter and Biochemical oxygen demand (BOD5). However, an increase in suspended solids was observed in some cases, especially on Farm 4 (34 %). These findings highlight that ditches are more suited to rapid nitrogen reduction, whereas ponds provide stable organic matter treatment but may require monitoring for solid accumulation. The combined use of both systems can enhance wastewater treatment outcomes and mitigate the environmental impact of intensive aquaculture. The results contribute to a better understanding of cost-effective and sustainable strategies for managing aquaculture effluents.